THE ANALYSIS OF INDIVIDUAL CAREER PLANNING IN MILLENNIALS GENERATION (STUDY IN PT. TELEKOMUNIKASI INDONESIA Tbk. AREA WITEL BANDUNG) - Muhamad Rizal; Rusdin Rusdin; Muhammad Mubian Nurlimang Munajat (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2019)
Millennials generation are the age group that will be lead an organization going forward. This generation has unique characteristics that are different from previous generations. These characteristics are both positive and negative. A company that wants to grow must be supported by the availability of qualified human resources and lead by a qualified leader. One way to achieve this is with career planning programs, especially individual career planning. The individual career planning process has a strong urgency in terms of improving the quality of human resources. Because individual career planning is concerned with the process of determining an individual career and the various steps to achieve that career without outside intervention. The object of this research is individual career planning on millennials generation by taking the locus of research at PT. Telekomunikasi Indonesia Tbk. Area Witel Bandung. The research method used is qualitative research method with descriptive research type. Data collection techniques use observation, interview and documentation. The results of this study indicate that millennials are already carrying out self-assessment activities and setting career goals well. However, feedback activity on reality has not been done well because employees have not comprehensively comprehended the assessment given by the company.